The molecular mechanism of plasma membrane H+-ATPases in plant responses to abiotic stress - Li, Jing; Guo, Yan; Yang, Yongqing (Journal of genetics and genomics, 2022)
Plasma membrane H+-ATPases (PM H+-ATPases) are critical proton pumps that export protons from the cytoplasm to the apoplast. The resulting proton gradient and difference in electrical potential energize various secondary active transport events. PM H+-ATPases play essential roles in plant growth, development, and stress responses. In this review, we focus on recent studies of the mechanism of PM H+-ATPases in response to abiotic stresses in plants, such as salt and high pH, temperature, drought, light, macronutrient deficiency, acidic soil and aluminum stress, as well as heavy metal toxicity. Moreover, we discuss remaining outstanding questions about how PM H+-ATPases contribute to abiotic stress responses.